ASSESSMENT OF EFFICACY OF VACCINOPROPHYLAXIS OF HAEMOPHILUS INFLUENZAE TYPE B INFECTION - O.A. Rychkova; N.V. Kazakevich; N.P. Sennikova; E.N. Semenyuk (Педиатрическая фармакология)
The article highlights the issue of preventing frequent acute respiratory infections in pre-school children attending day-care institutions who make up a large group of sick children with long-term conditions, according to the study results. Key bacterial causative agents of infection and inflammatory diseases of the respiratory system and ENT organs in this category of children are S. рneumoniae and Н. influenzae. Being an economically viable procedure, prevention of an infection caused by Н. Influenzae type B results in a dramatic decrease in the incidence of acute respiratory infections and severity of the infection process.Key words: Haemophilus influenzae, anti-haemophilus conjugate polysaccharide vaccine, children.